Quantifying infective endocarditis risk in patients with predisposing cardiac conditions. (17th November 2017) - Thornhill, Martin H; Jones, Simon; Prendergast, Bernard; Baddour, Larry M; Chambers, John B; Lockhart, Peter B; Dayer, Mark J
Abstract: Aims: There are scant comparative data quantifying the risk of infective endocarditis (IE) and associated mortality in individuals with predisposing cardiac conditions. Methods and results: English hospital admissions for conditions associated with increased IE risk were followed for 5 years to quantify subsequent IE admissions. The 5-year risk of IE or dying during an IE admission was calculated for each condition and compared with the entire English population as a control. Infective endocarditis incidence in the English population was 36.2/million/year. In comparison, patients with a previous history of IE had the highest risk of recurrence or dying during an IE admission [odds ratio (OR) 266 and 215, respectively]. These risks were also high in patients with prosthetic valves (OR 70 and 62) and previous valve repair (OR 77 and 60). Patients with congenital valve anomalies (currently considered 'moderate risk') had similar levels of risk (OR 66 and 57) and risks in other 'moderate-risk' conditions were not much lower. Congenital heart conditions (CHCs) repaired with prosthetic material (currently considered 'high risk' for 6 months following surgery) had lower risk than all 'moderate-risk' conditions—even in the first 6 months. Infective endocarditis risk was also significant in patients with cardiovascular implantable electronic devices. Conclusion: These data confirm the high IE risk of patients with a history of previous IE, valve replacement, or repair. However, IE risk in some 'moderate-risk' patients was similar to that of several 'high-risk' conditions and higher than repaired CHC. Guidelines for the risk stratification of conditions predisposing to IE may require re-evaluation.